Rail vehicle passing through a turnout: influence of the track elasticity (2014)
In recent years, the different transport systems have been largely improved. However, some problems need to be still solved if railways want to be the transport of the future. Among others: the high cost of infrastructure and its maintenance, the requirements to assure low noise levels and low transmission of vibration. The turnouts, one of the most critical elements on the track, are studied in this paper. Mathematical models have been developed in order to analyse in detail a vehicle passing through a turnout. These models are used to implement multibody models, which reproduce the phenomena of the vehicle/turnout interaction. The research analyses the validity and accuracy of multibody tools and how they could allow improving the design process of turnouts. In particular the influence of the turnout geometry and track elasticity has been investigated and also how these parameters could be optimized.